Unexpected costs: the impact of Long-Term Care Insurance on housing prices - Yang, Xin; Wen, Jing; Du, Weijie; Hu, Zhiding (Frontiers in Public Health, 2025)
IntroductionChina’s accelerated demographic aging has intensified scholarly interest in the institutional design and socio-economic impacts of the Long-Term Care Insurance (LTCI) pilot program. While its social and healthcare effects have been widely examined, little is known about its broader economic implications, particularly its impact on regional housing markets.MethodsUsing panel data for 285 Chinese cities from 2003 to 2022, this study employs a staggered difference-in-differences (DID) approach to estimate the causal effect of LTCI on housing prices. To ensure robustness, a series of additional tests are conducted, including propensity score matching (PSM), Bacon decomposition, system GMM estimation, placebo tests, and model averaging.ResultsThe findings indicate that the implementation of LTCI significantly increases housing prices. The migration of older adults into pilot cities serves as a key mechanism through which LTCI affects housing prices, as improved healthcare accessibility and enhanced living environments attract older adults and stimulate local housing demand. Heterogeneity analysis reveals that the effect is more pronounced in eastern regions, in areas with better environmental quality, and in cities offering home-based care services, while no significant differences are observed between pilot types.DiscussionThese results underscore the secondary economic impacts of long-term care policies. By linking LTCI to the migration of older adults and housing demand, this study deepens understanding of how welfare policies interact with housing markets in aging societies.